РОССИЯ ИМПЕРИЯСИ СУД-ҲУҚУҚ ОРГАНЛАРИ ТИЗИМИДА НОТАРИАЛ ИДОРАЛАР ФАОЛИЯТИ (ХIХ АСР ИККИНЧИ ЯРМИ – ХХ АСР БОШИ) (Scientific journal of the Fergana State University, 2023)
The article provides a review of the regulatory framework for the coordination of notarial activities in the Russian Empirein the second half of the XIX - early XX centuries and  the articles of the "Regulations on Notarial Parts", included in the first volume of the XVI Code of Laws. The need for personnel working in the notarial system and the requirements for them were studied. It also describes the requirements for a notary, his duties, their rights and obligations.